Carbonatite metasomatism overprinted by silicate melt metasomatism in the mantle beneath the West Eifel volcanic field - B. E. Bromley; S. Ma; S. Ma; C. S. J. Shaw (European Journal of Mineralogy)
The texture and mineral compositions of mantle xenoliths from the West Eifel volcanic field (WEVF) reveal three distinct mantle events. The first, identified in LREE-depleted and isotopically depleted anhydrous (type Ib) xenoliths, resulted from partial melting of fertile mantle around 2 Ga. The second event, marked by the formation of Ti-poor, LREE-rich clinopyroxene, amphibole, and phlogopite in hydrous type Ia xenoliths, is attributed to mantle metasomatism. The third event, evidenced by LREE-depleted and MREE-enriched clinopyroxene in olivine–clinopyroxenite veins and in more evolved hornblendite and phlogopite–clinopyroxenite veins that occur in type Ia xenoliths, is associated with the passage of primitive alkaline mafic magma related to the Quaternary host magmatism.